State ecological policy of Ukraine and legal mechanism of its formation and implementation - L.V. Serhiienko; O.M. Dziubenko; S.V. Ozhgo (Економіка, управління та адміністрування)
The paper identifies the strategical objectives of state ecological policy, which are declared in official documents of Ukraine for the stage of its independence and due to them, the vectors of the state ecological policy are characterized and their concretization is determined that witnesses not only about sharpening the ecological problems, but also their awareness by authority in the course of exercise of state administration activities. The state administration system significantly influences the protection, efficient use and reproduction of natural resources, the effective combination of functions of management of nature and environment defence, ensuring environmentally secure existence for the present and future generations. Such impact is carried out through the state ecological management, that is, the ecological policy formation and implementation. It is clarified that the legal mechanism is the base for the public administration in the field of the ecological policy implementation, and this mechanism must ensure the fulfilment of the scientifically substantiated principles for environment defence, the efficient use of natural resources, and the ecological security of human vital activities, establish the scientifically substantiated regulations of behavior for humans, enterprises and organizations in the area of ecology. The state ecological policy formation and implementation are inevitably connected with the formation and implementation of the corresponding policy on supranational and subjective levels, in particular, in terms of using the legal regulation as the policy tool and the base of its legal mechanism. Building the legal mechanism for the ecological policy formation and implementation with description of the legal regulation tools in terms of the policy levels allows to establish the interconnections among the levels, and determine the content of the present interaction. The author identifies and characterizes the interaction criteria for the detailed tools of the legal regulation among the policy levels.